2014
DOI: 10.1016/j.vaccine.2013.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of antibody responses by HIV envelope DNA and protein co-immunization

Abstract: Background Developing HIV Envelope (Env) vaccine components that elicit durable and protective antibody responses is an urgent priority, given the results from the RV144 trial. Optimization of both the immunogens and vaccination strategies will be needed to generate potent, durable antibodies. Due to the diversity of HIV, an effective Env-based vaccine will most likely require an extensive coverage of antigenic variants. A vaccine co-delivering Env immunogens as DNA and protein components could provide such co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 42 publications
5
33
0
Order By: Relevance
“…(i) SPR. Antibody concentrations in rabbit sera and in human plasma to autologous trimeric gp140 proteins 014_092603_G4 and 014_080406-C4a and to heterolo-gous trimer SF612 were determined on a Biacore T200 instrument (GE Healthcare, Piscataway, NJ) as previously described (50).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(i) SPR. Antibody concentrations in rabbit sera and in human plasma to autologous trimeric gp140 proteins 014_092603_G4 and 014_080406-C4a and to heterolo-gous trimer SF612 were determined on a Biacore T200 instrument (GE Healthcare, Piscataway, NJ) as previously described (50).…”
Section: Methodsmentioning
confidence: 99%
“…Longitudinal plasma samples were tested for neutralization of four clade B heterologous viruses, one clade A heterologous virus, and two clade C heterologous viruses in a TZM-bl assay. Neutralization data are expressed as ID 50 , the plasma dilution that neutralized 50% of the infecting virus. Neutralization breadth scores were determined as previously described (72).…”
Section: Fig 2 Longitudinal Heterologous Neutralizing Antibodies In Smentioning
confidence: 99%
See 1 more Smart Citation
“…These data showed that co-delivering DNA and protein can increase antibody responses to Env. Hence, this approach has the potential to simplify vaccine regimens by inducing higher antibody responses using fewer vaccinations, an advantage for a successful HIV vaccine design [57].…”
Section: Heterologous Prime-boost Strategiesmentioning
confidence: 99%
“…Due to the diversity of HIV, an effective viral envelop (Env)-based vaccine will likely need a broad coverage of antigenic variants. A vaccine codelivering Env immunogens as DNA and protein components could provide such coverage [14]. This review is focused on optimization of DNA-based vaccines using different strategies against HIV infections.…”
Section: Introductionmentioning
confidence: 99%